The Renaissance-An Age of Enlightenment - Shukla, Dr. Shikha (International Journal of Psychosocial Rehabilitation, 2020)
Renaissance movement is remarkable for creating a new awareness to the life and for widening the horizon of the people. The light of Renaissance came first of all to Italy and then France and lastly to England. The Renaissance period was the succeeding epoch of the Middle Ages which was the gap defining the classical and modern period. The widespread influence of Renaissance movement was felt upon the literature and philosophy of England during 16th Century